Fungal Diversity in Barley Under Different Storage Conditions - Cao, Dongmei; Lou, Yuhao; Jiang, Xiujie; Zhang, Dongjie; Liu, Junmei (Frontiers in Microbiology, 2022)
The diversity of fungi in barley in simulated storage environments was analyzed. Barley was stored at different temperatures (15℃, 25℃, 35℃) and relative humidity (55%, 65%, 75%, 85% RH) for 180 and 360 days. Alpha diversity, Beta diversity, species composition, and species differences were analyzed using Illumina Hiseq technology. The fungal communities in all barley samples before and after storage belonged to three phyla, 18 classes, 39 orders, 71 families, 103 genera, and 152 species. The relative abundance of the dominant phylum Ascomycota was 77.98%–99.19%. The relative abundance of Basidiomycota was 0.77%–21.96%. At the genus level, the dominant genera of fungi in barley initially included Fusarium, Aspergillus, Microdochium, Alternaria, and Epicoccum. After 360 d storage, the dominant genera became Epicoccum, Alternaria, Bipolar, Cladosporium, Fusarium, and Aspergillus. According to Venn diagrams and PCoA analysis, the fungal community diversity in barley initially was much larger than in barley stored at different temperatures and humidity. The application of PLS-DA analysis could accurately distinguish between barley stored for 180 and 360 days. Some high temperature and high humidity environments accelerated storage. The dominant genera differed in different storage conditions, and constantly changed with increasing storage duration. Epicoccum was one of the dominant genera after longer storage periods. This study provides theoretical support for optimizing safe storage conditions in barley.